Characterization of green synthesized silver nanoparticles from Falconeria insignis Royle and its antimicrobial activity - M. S. Amithalal; Mari Sumayli; E. S. Abhilash; Yehia Hazzazi; Ugur Azizoglu; Sajjad Sajjad; A. El-Shabasy (PLoS ONE, 2026)
Falconeria insignis Royle leaf extract was utilized for the first time as a natural reducing and stabilizing agent in a green precipitation method to synthesize silver nanoparticles devoid of hazardous chemicals. A change in hue from light yellow to pale brown showed that AgNPs were formed. This was confirmed by UV-visible spectroscopy, which showed a unique surface plasmon resonance peak at 300–350 nm. The FTIR investigation found hydroxyl, carbonyl, amide, C–N, and C–O functional groups. This showed that proteins, phenolics, and flavonoids can bio-reduce and cap. XRD confirmed that the silver was nanocrystalline and had a mean crystallite size of 19 nm. The SEM showed predominantly non-spherical and heterogeneous in overall shape. Biogenic AgNPs are different from crude extract and silver nitrate, had much higher antibacterial activity against Staphylococcus aureus . ANOVA verified statistically significant differences between treatments. According to these findings, F. insignis Royle is a viable, sustainable bioresource for the manufacture of green AgNP with possible biomedical antibacterial uses.